Luther strode ebook - Jordan, Justin (The Legacy of Luther Strode (2015)., 2018)
The LUTHER STRODE Saga ends here. Luther and Petra are on the road that will lead them to the final confrontation with Cain, the first murderer and architect of Luther's pain. Collects THE LEGACY OF LUTHER STRODE #1-6. Author: Justin Jordan. Illustrator: Tradd Moore, Felipe Sobreiro . 2016 Justin Jordarn & Tradd Moore.